2019
DOI: 10.1111/imm.13125
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte isolation techniques significantly impact the phenotype of both isolated monocytes and derived macrophages in vitro

Abstract: Summary Monocyte‐derived macrophages (MDMs) generated from peripheral blood monocytes are widely used to model human macrophages for in vitro studies. However, the possible impact of different isolation methods on the resulting MDM phenotype is poorly described. We aimed to investigate the effects of three commonly used monocyte isolation techniques on the resulting MDM phenotype. Plastic adhesion, negative selection, and CD14pos selection were compared. Monocyte‐derived macrophages were generated by 5‐day cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 27 publications
10
97
0
Order By: Relevance
“…Cells were cultured at 5.0 × 10 5 cells/ml with addition of IL-4 and SCF twice a week. Purity of macrophage cultures were routinely checked to be > 85% 70 . For imaging, cells were used after 3 days in culture, washed twice with PBS and seeded on 18 mm diameter microscope cover glass for imaging (VWR, Darmstadt, Germany) in PBS containing Ca 2+ (Gibco, Carlsbad, CA, USA) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured at 5.0 × 10 5 cells/ml with addition of IL-4 and SCF twice a week. Purity of macrophage cultures were routinely checked to be > 85% 70 . For imaging, cells were used after 3 days in culture, washed twice with PBS and seeded on 18 mm diameter microscope cover glass for imaging (VWR, Darmstadt, Germany) in PBS containing Ca 2+ (Gibco, Carlsbad, CA, USA) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of sCD163-α-syn binding was studied using Microscale Thermophoresis (MST). Monocyte-derived macrophages (MDMs) from isolated and maturated human monocytes 25 were stimulated with 100nM, 1µM, or 5µM monomeric or fibrillar α-syn for 6 or 24 hours, followed by sCD163-ELISA measurement in supernatants.…”
Section: Methodsmentioning
confidence: 99%
“…Both human peripheral blood mononuclear cells (PBMCs) and mouse bone marrow cells were stimulated by M‐CSF, and we found that Paqr11 expression was highly elevated during the differentiation (Figure 1D,E), indicating a positive correlation between Paqr11 expression and monocyte‐to‐macrophage differentiation. As control experiments, we found that Cd14 expression was reduced during M‐CSF‐induced differentiation in human PBMCs 30 (Figure 1D) and Adgre1 expression was increased during the differentiation in mouse bone marrow cells 31 (Figure 1E).…”
Section: Resultsmentioning
confidence: 78%